Determination of the field of constrain forces representing the effect of the impeller's blading - Czibere, Tibor; Kalmár, László (Computer Assisted Methods in Engineering and Science, 2023)
The aim of this paper is to present a numerical method to determine a field of constrain forces which hydrodynamically represents the effect of the blading of the impeller of a radial-flow pump. The field of constrain forces are perpendicular to the stream surfaces of the relative velocity field and congruent to the blade surface of the impeller. The calculation of the constrain force field is based on the solution of the inverse problem of the hydrodynamic cascade theory. In the determination of the constrain force it is supposed that the frictionless and incompressible fluid flow is completely attached to the blade surfaces he constrain force field can be calculated by the change of the moment of momentum in the absolute inviscid fluid flow which depends on the state of the pump. Knowing the constrain force field it is possible to calculate the distributions of the relative velocity, pressure and energy loss on the mean stream surface (F) of the impeller by solving the governing equations of the viscous relative flow. By calculating the energy loss belonging to different volume rates an approximate real head-discharge characteristic of the impeller also can be computed.